COMPETENCY, CULTURAL ORGANIZATION, WORK MOTIVATION AND PERFOMANCE OF MILITARY TEACHER AT PUSAT PENDIDIKAN POLISI MILITER KODIKLATAD TNI AD - Sain Mustain; Ony Djogo (JEES: Journal of Economic Empowerment Strategy, 2021)
Competency, cultural organization, work motivation and performance of military teacher as an important part of education process. The goal of this research to describe at Pusat Pendidikan Polisi Militer Kodiklatad TNI AD. Total populations are 190 persons and samples are 129 person who are decided according to Slovin Formula. Correlations score between competency and cultural organization is 0,907 (very strong), cultural organization and work motivation is 0,871 (very strong), competency and performance is 0,910 (very strong), competency and motivation is 0,876 (very strong), compensation and performance is 0,930 (very strong) and motivation and performance is 0,872 (very strong). Result of this equation showed when Employee Performance without competency, cultural organization, motivation, performance showed a score only 7,693. Competency, cultural organization, motivation and performance at the level good and could be improved to reach their excellent performance.